Contagious Bank Runs: Evidence from the 1929–1933 Period - Saunders, Anthony; Wilson, Berry (Journal of Financial Intermediation, 1996)
This paper empirically examines contagion effects of bank failures by analyzing the behavior of deposit flows in a sample of failed and healthy banks over the 1929–1933 period. We find evidence of contagion for 1930–1932, while none seems to have existed in 1929 or 1933. In addition, the pace of contagion accelerated over 1930–1932. We find that even during 1930–1932, failing-bank deposit outflows exceeded those at a matched control sample of nonfailing banks. This finding is consistent with the presence of a significant number of informed depositors who distinguished among ex ante failing and nonfailing banks.Journal of Economic LiteratureClassification Number: G21.